2016
DOI: 10.3892/mco.2016.978
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety of BRAF and MEK inhibitors (vemurafenib, dabrafenib and trametinib) in first-line therapy for BRAF-mutated metastatic melanoma

Abstract: Abstract. A retrospective observational study was conducted on patients diagnosed with serine/threonine-protein kinase B-Raf (BRAF)-mutated metastatic melanoma, who underwent first-line therapy with BRAF and mitogen-activated protein kinase kinase (MEK) inhibitors (vemurafenib, dabrafenib or a combination of dabrafenib and trametinib) at the Miguel Servet University Hospital (Zaragoza, Spain) between November, 2011 and August, 2015. The aim of this study was to analyse the toxicity produced by BRAF and MEK inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…Finally, the risk of infection was not increased with the use of BRAF and MEK inhibitors in a meta-analysis [74] and in two reviews on the management of most commonly observed toxicities [75,76].…”
Section: Available Clinical Datamentioning
confidence: 95%
See 1 more Smart Citation
“…Finally, the risk of infection was not increased with the use of BRAF and MEK inhibitors in a meta-analysis [74] and in two reviews on the management of most commonly observed toxicities [75,76].…”
Section: Available Clinical Datamentioning
confidence: 95%
“…Acalabrutinib (ACP-196, Acerta Pharma BV) is a secondgeneration, more selective, irreversible BTK inhibitor with improved pharmacologic features, including a more favourable plasma exposure, rapid oral absorption, short half-life and absence of irreversible targeting to alternative kinases. Compared to ibrutinib, which also targets ERK and other kinases, acalabrutinib exerts a more selective action on BTK [75]. Acalabrutinib has obtained a breakthrough therapy designation from the FDA for the treatment of patients with mantle-cell lymphoma who have received at least one prior therapy.…”
Section: Bruton Tyrosine Kinase Inhibitors: Ibrutinib and Acalabrutinibmentioning
confidence: 99%
“…In particular, BRAF V600E mutation was found in ~ 50% of all cutaneous melanomas (Davies et al, ). Targeted therapies, such as vemurafenib and dabrafenib (Rissmann, Hessel, & Cohen, ), which are small molecular inhibitors of BRAF (Morris & Kopetz, ) that block the signaling of the MAPK pathway and decrease melanoma cell proliferation, have proven effective at improving the disease‐free survival (DFS) of the BRAF V600 mutant population (Banzi et al, ; Cebollero, Puertolas, Pajares, Calera, & Anton, ). It was also reported that melanoma genomes have the highest tumor mutation burden (TMB) of any cancer types (Alexandrov, Nik‐Zainal, Wedge, Aparicio, et al, ; Cancer Genome Atlas, ) and that a high TMB predicts a favorable outcome for immune checkpoint blockade therapies (Chan, Wolchok, & Snyder, ; Goodman et al, ; Robert, Schachter, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials reported that diarrhea, anorexia, nausea, and vomiting are common adverse events frequently associated with the use of a combination of BRAF and MEK inhibitors in daily clinical practice, thus requiring early and appropriate managements to avoid unnecessary dose reductions and transitory or definitive treatment discontinuations. 7 Therefore, there is a need to master the characteristic features, incidence, and relative risk (RR) of significant adverse events to take adequate prevention and intervention as early as possible. 8 Hence, in this study, we have performed a meta-analysis to assess the therapeutic efficacy and safety of combined BRAF and MEK inhibition in patients with malignant melanoma and to provide treatment recommendations for these symptoms.…”
Section: Introductionmentioning
confidence: 99%